2006
DOI: 10.1093/heapro/dal048
|View full text |Cite
|
Sign up to set email alerts
|

Gender and health promotion: A multisectoral policy approach

Abstract: Women and men are different as regards their biology, the roles and responsibilities that society assigns to them and their position in the family and community. These factors have a great influence on causes, consequences and management of diseases and ill-health and on the efficacy of health promotion policies and programmes. This is confirmed by evidence on male-female differences in cause-specific mortality and morbidity and exposure to risk factors. Health promoting interventions aimed at ensuring safe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 20 publications
3
119
0
7
Order By: Relevance
“…Gender relations are defined by different roles and responsibilities assigned by society to men and women (Ostlin et al 2006). The traditions and cultures delineate tasks and responsibilities of individuals within nomadic society, and sketch the roles of women within the family and community.…”
Section: Predisposing Characteristicsmentioning
confidence: 99%
“…Gender relations are defined by different roles and responsibilities assigned by society to men and women (Ostlin et al 2006). The traditions and cultures delineate tasks and responsibilities of individuals within nomadic society, and sketch the roles of women within the family and community.…”
Section: Predisposing Characteristicsmentioning
confidence: 99%
“…Although this may due to the welldocumented gender-based reporting bias on physical function, 45 it is also possible that this discrepancy could be attributed to the differences in biology, control over resources and their decision making power in family and community, as well as the roles and responsibilities that society assigns to them. 46 Individuals in this study with higher levels of educational attainment, individuals with a higher level of occupation, and members of high income households reported higher physical function. Previous studies have shown that income and education are likely to be closely linked, but with one influencing the other via distinct aetiological pathways.…”
Section: Accepted M Manuscriptmentioning
confidence: 60%
“…If gender stereotyping is indeed a cause of male reticence then individual change is unlikely in the absence of structural change (Cameron and Bernardes, 1998). Public health policies, however, tend to be gender-blind, essentially because of a presumption that gender-sensitivity in services is unnecessary and concerns about appearing discriminatory (Ostlin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%